The dynamics of Carat Indonesia's solidarity in anonymous interactions on X - Nabila Zikri Ramadhanti; Nanik Rahmawati; Nikodemus Niko (Privietlab, 2025)
This study aims to understand how solidarity is formed and maintained among members of the Boy Group Seventeen fan community, Carat Indonesia, on social media X (formerly Twitter,we use the term